2021
DOI: 10.1590/2177-6709.26.3.e2119300.oar
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic analysis of midpalatal suture prior to rapid maxillary expansion

Abstract: Introduction: In Orthodontics and Facial Orthopedics, the timing of treatment onset may be critical and individual analysis should be applied to promote a favorable treatment planning. In this study, individual analysis of midpalatal suture (MS) and palatal measurements were performed in teenagers and young adult patients treated with rapid maxillary expansion (RME). Description: Twenty-six patients submitted to RME with a tooth-supported appliance (Hyrax) were evaluated. The inclusion criteria were: minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Several studies have shown that the volume of the nasal cavity increases after rapid maxillary expansion 14 . In addition, the area of ​​the upper airways and nasopharynx increases, 15–18 as does the transverse dimension of the maxillary complex, 14 results that were obtained in the present clinical case.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have shown that the volume of the nasal cavity increases after rapid maxillary expansion 14 . In addition, the area of ​​the upper airways and nasopharynx increases, 15–18 as does the transverse dimension of the maxillary complex, 14 results that were obtained in the present clinical case.…”
Section: Discussionsupporting
confidence: 69%
“…the type of expansion. This is because the teeth subjected to compression have an increased root angulation, a fact that indicates the need to apply a movement preferably of tilting, not of translation as was usual before [25].…”
Section: Resultsmentioning
confidence: 99%
“…The maturation and density of the midpalatal suture (MS) were assessed by Christovam et al 29 Patients with greater MS density (MSD) had a smaller sagittal area than those with lower density (MSD < 0.75). When compared with stage C, patients in stages D and E MS maturation had a lower sagittal area and intermediate thickness.…”
Section: Discussionmentioning
confidence: 99%